New records of hoverflies (Diptera: Syrphidae) and the rediscovery of Primocerioides regale Violovitsh for the fauna of Serbia - van Steenis, Jeroen; Nedeljković, Zorica; Tot, Tamara; van der Ent, Leendert-Jan; van Eck, André; Mazánek, Libor; Šebić, Anja; Radenković, Snežana; Vujić, Ante (Biologia Serbica, 2019)
In preparation for the IUCN workshop on the European Red List of Syrphidae from April 4th-16th 2019, a total of 59 hoverfly species were collected in Novi Sad and on Fruška Gora Mountain (Serbia). Among the identified species, one species is possibly new to science, Brachypalpus aff. valgus, and six other species are new to the fauna of Serbia: Brachyopa grunewaldensis, B. silviae, Criorhina pachymera, Epistrophe cryptica, Psilota anthracina and Sphiximorpha petronillae. During the preparation of this work, a photo taken in Belgrade confirmed the occurrence of Primocerioides regale in Serbia. Additionally, six rarely recorded species for the fauna of Serbia were collected: Brachyopa maculipennis, B. plena, Criorhina floccosa, Epistrophella coronata, Mallota fuciformis and Sphiximorpha subsessilis. The list of new and rare species and information on behaviour and habitats are provided. The value of Kamenički Park, Novi Sad, for saproxylic hoverflies is discussed and possible conservation measurements are proposed to retain this treasury of rare and possibly threatened species. The previously proposed co-occurrence of Sphiximorpha petronillae and the European velvety tree ant (Liometopum microcephalum (Panzer, 1798)) is also discussed.